Аналіз порушень серцевого ритму у пацієнтів з різними формами ішемічної хвороби серця: результати 5-річного спостереження = Analysis of arrhythmic disorders in patients with coronary heart disease: results of 5 years follow-up investigation - D. M. Sebov (Kazimierz Wielki University, 2015)
Sebov D. M. Аналіз порушень серцевого ритму у пацієнтів з різними формами ішемічної хвороби серця: результати 5-річного спостереження = Analysis of arrhythmic disorders in patients with coronary heart disease: results of 5 years follow-up investigation. Journal of Education, Health and Sport. 2015;5(10):11-18. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.31835 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A11-18 https://pbn.nauka.gov.pl/works/644612 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015.   УДК 616.12-008.318-02:616.12-005.4-03   АНАЛІЗ ПОРУШЕНЬ СЕРЦЕВОГО РИТМУ У ПАЦІЄНТІВ З РІЗНИМИ ФОРМАМИ ІШЕМІЧНОЇ ХВОРОБИ СЕРЦЯ: РЕЗУЛЬТАТИ 5-РІЧНОГО СПОСТЕРЕЖЕННЯ ANALYSIS OF ARRHYTHMIC DISORDERS IN PATIENTS WITH CORONARY HEART DISEASE: RESULTS OF 5 YEARS FOLLOW-UP INVESTIGATION   Д. М. Себов D. M. Sebov   Одеський Національний медичний університет, Одеса, Україна Odesa national medical university, Odesa, Ukraine   Summary The study involved 434 patients with clinical signs of stable coronary artery disease, including 217 patients with initial coronary atherosclerosis and 217 patients with intact coronary arteries (coronary syndrome X), taking into account the presence of severe coronary tortuosity. The 24-hours holter ECG-monitoring and subsequent 5 years follow-up observation with the calculation of the cumulative number of cardiac arrhythmias performed. According to 24-hours holter ECG-monitoring the phenomenon of severe coronary tortuosity without atherosclerotic lesions recognized as an additional factor for  cardiac arrhythmias development (p=0.0001) in patients with symptomatic coronary heart disease. According to 5-year analysis, the phenomenon of severe coronary tortuosity significantly worsens the prognosis of significant cardiac arrhythmias occurrence, and the number of first onset of cardiac arrhythmias was significantly higher than the patients with coronary heart disease and initial coronary atherosclerosis.   Key words: arrhythmias, coronary X syndrome, severe coronary tortuosity.   Резюме Обстежено 434 пацієнтів, хворих з клінічними ознаками стабільної ішемічної хвороби серця, зокрема 217 пацієнтів з початковим коронарним атеросклерозом та 217 пацієнтів з інтактними коронарними артеріями (коронарний синдром Х) з урахуванням присутності вираженої звитості коронарної артерії, яким проведено холтерівське ЕКГ-моніторування та наступне 5-річне спостереження з обчисленням кумулятивної кількості порушень серцевого ритму.             За даними добового холтерівського ЕКГ-моніторування феномен вираженої звитості коронарних артерій без атеросклеротичного ураження при симптоматичній ішемічній хворобі серця розпізнаний як додатковий фактор розвитку порушень серцевого ритму (р=0,0001).             За даними 5-річного аналізу у хворих на ішемічну хворобу серця та коронарний синдром Х, присутність феномену вираженої звитості коронарних артерій достовірно погіршує прогноз виникнення гемодинамічно значущих порушень серцевого ритму в порівнянні з пацієнтами без нього, а кількість вперше виниклих порушень серцевого ритму була достовірно вищою за хворих на ІХС з початковим атеросклерозом коронарних артерій.   Ключові слова: порушення ритму серця, коронарний синдром Х, виражена звитість коронарних артерій.